Are socio-demographic and building characteristics associated with noise complaints? - Yildirim, Yalcin; Arefi, Mahyar (Routledge Journals, Taylor & Francis Ltd, 2023)
This study explores the nexus between socio-demographics and building attributes on the one hand, and the 311 non-emergency services - a state-of-the-art self-reported data source reflecting the residents' noise complaints on the other. While inevitable and bothersome regardless of the location or lifestyle, noise demonstrates people's exposure to it on different scales. This study performs various spatial and statistical analyses integrating spatial, socio-demographic and building factors associated with noise complaints in Dallas, Texas. These analyses reveal the broader environmental and urban planning implications associated with noise. The results confirm that socio-demographic characteristics show different relationships at various degrees. Vulnerable populations do not opt for reporting noise complaints while building-related attributes, particularly the number of building permits and businesses better explain the association between noise complaints and building characteristics. The study also proposes the key takeaways for developers, planning practitioners and local authorities.
Keywords: Building; socio-demographic; vulnerable population; noise complaints; self-report